1956
DOI: 10.1002/aic.690020427
|View full text |Cite
|
Sign up to set email alerts
|

Ignition of solid propellants by forced convection

Abstract: Experimental data are reported for the ignition of single grains of solid propellant in a stream of gas at high temperature. The investigation encompassed gas temperatures from 578" to 1,O7O0K., gas velocities corresponding to free-stream Reynolds numbers from 156 to 624, a complete range of oxygen-nitrogen m e s , and a few oxygen-carbon dioxide mixtures. Pyrocellulose and double-base propellants were tested. The grains were approximately 1/8 in. in diameter and extended through the gas stream, so that igniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1962
1962
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Linear surface ignition temperatures have also been calculated for the data of Brier and coworkers (6) on the ignition by forced convection of M2 in 20% oxygen-80% nitrogen mixtures. For these calculations, the maximum local heat transfer coefficient was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Linear surface ignition temperatures have also been calculated for the data of Brier and coworkers (6) on the ignition by forced convection of M2 in 20% oxygen-80% nitrogen mixtures. For these calculations, the maximum local heat transfer coefficient was used.…”
Section: Methodsmentioning
confidence: 99%
“…Cook and Olson (7) arrived at a similar conclusion. Brier and coworkers (6) reported that increasing oxygen content results in a decrease in ignition time. One may conclude that under conditions of forced convection, gas phase kinetics contribute significantly to the over-all kinetics of ignition to flame burning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An investigation, in connection with the onset of the U.S. space program, of the ignition of solid propellants by a stream of very hot gas, revealed that the process depended critically on chemical reactions in the gas-phase (Churchill et al). 1 This unexpected finding prompted a subsidiary investigation of the contribution of the energetic chemical reactions of combustion to convective heat transfer. It was decided to pursue this diversionary effort in the context of combustion inside a tube because of the extensive database for forced convection without reaction in tubular flow.…”
Section: Promptingsmentioning
confidence: 99%
“…This may have been due to a partial decomposition of the propellant without the formation of flame. 11 is known that the gentle heating by a flameless ignition source can cause nitrocellulose and some nitrocellulose-containing propellants to decompose without the formation of flame in a fizz-type of burning (Churchill et al, 1956;Roth and Wachtell, 1962). The decomposition reaction proceeds in a smoldering-like manner.…”
mentioning
confidence: 99%